2012
DOI: 10.1002/hbm.21408
|View full text |Cite
|
Sign up to set email alerts
|

Seeing touch and pain in a stranger modulates the cortical responses elicited by somatosensory but not auditory stimulation

Abstract: Viewing other's pain inhibits the excitability of the motor cortex and also modulates the neural activity elicited by a concomitantly delivered nociceptive somatosensory stimulus. As the neural activity elicited by a transient nociceptive stimulus largely reflects non nociceptive-specific, multimodal neural processes, here we tested, for the first time, whether the observation of other's pain preferentially affects the brain responses elicited by nociceptive stimulation, or instead similarly modulates those el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 81 publications
2
10
0
Order By: Relevance
“…CLARA is a novel iterative source analysis method which operates by performing a weighted LORETA (Low Resolution Electromagnetic Tomography Analysis, [ 52 ]) on each iteration, followed by source space reduction. Compared to the standard LORETA method, CLARA reduces the blurring of the estimated sources while maintaining the advantages of a predefined distributed source model, thus making it easier to obtain a relatively focal distribution of source activation [ 53 55 ]. It combines the advantages of discrete and distributed source analysis by employing distributed source analysis with a shrinking of the source space.…”
Section: Methodsmentioning
confidence: 99%
“…CLARA is a novel iterative source analysis method which operates by performing a weighted LORETA (Low Resolution Electromagnetic Tomography Analysis, [ 52 ]) on each iteration, followed by source space reduction. Compared to the standard LORETA method, CLARA reduces the blurring of the estimated sources while maintaining the advantages of a predefined distributed source model, thus making it easier to obtain a relatively focal distribution of source activation [ 53 55 ]. It combines the advantages of discrete and distributed source analysis by employing distributed source analysis with a shrinking of the source space.…”
Section: Methodsmentioning
confidence: 99%
“…However, Godinho with co-workers reported that an increase in the intensity of pain to noxious electric stimuli, that occurred when observing bodily injuries, was accompanied by modulation of late components of somatosensory evoked potentials and the activity in the prefrontal cortex, pregenual cingulate cortex, and temporo-parietal-occipital junction, but not in the somatosensory cortex or other core areas of the pain matrix (Godinho et al 2006, 2012). 1 Interestingly, in contrast to pain elicited by electric pulses or sustained heat, pain sensations evoked by brief laser heat stimuli were not changed during observation of hands undergoing needle penetrations in two studies (Valeriani et al 2008; Valentini et al 2012). It is thus possible that perception of brief heat pain is not affected by seeing pain in others.…”
Section: How Pain In Others Influences the Processing And Perception mentioning
confidence: 98%
“…The pain matrix is composed of lateral (sensory–discriminatory involving areas such as the primary and secondary somatosensory cortex, thalamus, and posterior parts of the insula) and medial (affective–cognitive–evaluative involving areas such as the anterior parts of the insula, anterior cingulate cortex, and prefrontal cortex) neuroanatomical components 37. Empathy for pain induces not only affective–motivational representations, but also sensory–discriminatory representations in the brain 810. Thus, we can use empathic pain to explore the pain system without inducing actual pain.…”
Section: Introductionmentioning
confidence: 99%